Dietetic Sesame Paste Cream Using Sucrose Replacers (Isomalt, Rebaudioside a, Erythritol) - Elahe Dehghan; Behzad Mohammadi (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2023)
Introduction Sesame paste is a product that is obtained by mixing Ardeh obtained from peeling of Sesame seeds with sugar or other sweeteners and flavorants such as cardamom and vanilla. Each 100 grams of this nutritious product contains 558 kcal and providing 17% of the daily calcium need, 100% for iron and 26% for protein. Sesame cream /Ardeh cream provides 478 kcal per 100 grams. Ardeh cream is also a good alternative to chocolates with artificial colors, so it is a very good choice in cases of hypoglycemia, such as before the exam session of students or during heavy excersize such as mountaineering. Sugar substitutes are compounds that, like sugars, are used to sweeten foods, except that they are not digested without the need for metabolized insulin, or are digested sparingly and therefore have little caloric value. The diet products are usually based on reducing calorie intake, which today, the growing interest of people in eating healthy diet has led to an increase in their desire to consume low-calorie products. Patients with diseases caused by sugar consumption such as diabetes, hypertension and hyperlipidemia, osteoporosis, obesity, etc. tend to use artificial sweeteners such as saccharin, aspartame, cyclamate and acesulfame. Materials and Methods Hydrogenated oil, Skim milk powder, Whey powder, Soy lecithin, Potassium dichromate, Ethanol, Ardeh , Erythritol, Isomalt Powder, Ribodioside a, Sugar  Stable micro histometer systems, Ballmer, Memmert model digital scale, Autoclave, Oven, N Hexane, Desiccator, Soxhlet device, 500 cc balloon, Peptone water, Dichlorine-Rose Bengal Chloramphenicol Agar (DG18), coax reagent, EC broth culture medium, lauryl sulfate culture medium, pH meter with measuring accuracy of 0.1%, 0.1 N sulfuric acid solution, Potassium sulfate, dioxide Selenium, boric acid solution, crystallized copper sulfate, aluminum plate were used in this study . First, to prepare a control sample, raw materials such as flour, oil and sugar were added to the mixer and mixed together, then the rest of the ingredients were added and mixed inside the machine to make the cream uniform and homogeneous. Then it was transferred to the filter and packed in the desired containers. Sugar substitutes were used for the rest of the samples. Results and Discussion The prevalence of obesity and diabetes has increased dramatically in recent years, forcing consumers to look for low-calorie sweeteners. Replacing low-calorie sweeteners with sucrose results in low-calorie,  and healthy foods. The aim of this study was to present a new formulation using isomalt, ribadioside a, erythritol as sucrose substituents and to investigate its effect on chemical, physical and sensory properties of substituted samples compared to the control sample. The use of sucrose substituents was effective in improving some physicochemical properties of Ardeh so that the moisture content of the substituted samples increased. The results of histological examination also showed that the replaced samples had softer tissue than the control sample, which was due to the weakening of tissue stability by sucrose substitutes. The results of sensory properties based on aroma, taste, odor and texture also showed that sample 2 with the formula 25% sucrose, 6.25% isomalt, 0.003 ribodiozide obtained the highest score in terms of overall acceptance. The reason for the decrease in the general acceptance of the samples replaced with complete elimination of sucrose is the lack of regulation of the desired sweetness by these alternatives. The results of microbial analysis of samples also showed that sugar substitutes have no effect on the microbial properties of Ardeh. According to the obtained results, sample 2 with 25% sucrose, 6.25% isomalt, 0.003% ribodioside a is the best combination and a healthy and low calorie snack.